"We want to hear your problems and fix them": A case study of pandemic support calls for home health aides. Issue 2 (3rd April 2022) - Tsui, Emma K.; LaMonica, Marita; Hyder, Maryam; Baron, Sherry
ABSTRACT: Home health aides and home care agencies, who operate in a high work stress environment under normal conditions, were placed under extraordinary demands during the COVID-19 pandemic. In this paper, we examine the unfolding effort at one agency in New York City to offer phone-based support calls to aides. We used a qualitative, single case study design involving semi-structured interviews with call staff and agency leaders (n = 9) and analysis of one year of thematic notes from the calls. We found that the calls resulted in multidirectional communication between agency staff and aides, an increased sense of empathy among staff, and a greater integration of aides into the agency's overall infrastructure. We explore how these calls might contribute to aide retention, worker voice, and mental health. We note the facilitators and barriers to implementing this type of job-based support to help other agencies that may be considering similar models.